Permutations of Candy Crush Game - Yudrum, Narit; Kamsripol, Phetnaree; Pongkamonsat, Surakrai; Mato, Uthoomporn (Journal of Science Ladkrabang, 2024)
Candy Crush game was launched on Facebook in 2012 and it has been a famous game which is played on various mobile and web platforms. In Candy Crush game, differently colored candies are arranged in a grid. To clear a level, the player need to swap adjacent candies in order to match three or more candies of the same color. In this article, we show the permutations of the candies in Candy Crush game for students or the person who interested in combinatorics to get the new examples of applying permutations to solve something through the fun game.